8(2x-1)=3(4x+8)+4

Simple and best practice solution for 8(2x-1)=3(4x+8)+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(2x-1)=3(4x+8)+4 equation:


Simplifying
8(2x + -1) = 3(4x + 8) + 4

Reorder the terms:
8(-1 + 2x) = 3(4x + 8) + 4
(-1 * 8 + 2x * 8) = 3(4x + 8) + 4
(-8 + 16x) = 3(4x + 8) + 4

Reorder the terms:
-8 + 16x = 3(8 + 4x) + 4
-8 + 16x = (8 * 3 + 4x * 3) + 4
-8 + 16x = (24 + 12x) + 4

Reorder the terms:
-8 + 16x = 24 + 4 + 12x

Combine like terms: 24 + 4 = 28
-8 + 16x = 28 + 12x

Solving
-8 + 16x = 28 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
-8 + 16x + -12x = 28 + 12x + -12x

Combine like terms: 16x + -12x = 4x
-8 + 4x = 28 + 12x + -12x

Combine like terms: 12x + -12x = 0
-8 + 4x = 28 + 0
-8 + 4x = 28

Add '8' to each side of the equation.
-8 + 8 + 4x = 28 + 8

Combine like terms: -8 + 8 = 0
0 + 4x = 28 + 8
4x = 28 + 8

Combine like terms: 28 + 8 = 36
4x = 36

Divide each side by '4'.
x = 9

Simplifying
x = 9

See similar equations:

| t=35t-16t^2 | | -2(4+p)=-18 | | E=4x(7+3x) | | 3x^2y^2+6x^2y-9xy= | | -5.7x-1.9y=11.4 | | (7x+3)+(9n+3x)+(-2-2n)= | | 5+7x=-4 | | -38=-2(-4ed-24) | | -30=-6(5+p) | | 6x+15=3y-3 | | -3(-x)-7=1+x | | 28=f-3 | | 6000=4 | | 6(p-8)=-42 | | -30+(150)=X | | 24=2(-x+3) | | 2(3y+4+2)= | | 17+10x-3=-3(x-6) | | 14x+8+10x+28=180 | | 9x+5=12x-19 | | 6-(-7+x)=42 | | 600=2x+3y | | -6(5n+5)=-120 | | 8x-27=4x+33 | | 140=90+m | | 12-4x=-5x+22 | | 12x^2+26x-10=0 | | 2(g+4)+5g-1= | | 3n+28=200 | | 0.75n+1.29=7.00 | | x(2x-5)(x^2-3)(5x^3-8)=0 | | -3x=-5x+22 |

Equations solver categories